2016
DOI: 10.5861/ijrsll.2016.1562
|View full text |Cite
|
Sign up to set email alerts
|

The effect of songs on vocabulary retention of preschool young English language learners

Abstract: The present study was an attempt to investigate the effectiveness of teaching English vocabulary through song to preschool young English Language Learners in Aligoodarz, Iran.The participants of the study consisted of 103 preschool young learners, who were divided into two groups of experimental group and control group. The experimental groups were consisted of 62 young learners and the control groups were consisted of 51 young learners at the age of six. The experimental groups were instructed using song and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
(20 reference statements)
2
7
0
Order By: Relevance
“…This finding corresponds with previous studies in which English learners could remember greater words following musical mnemonics sessions than non-musical learners (Abdolmanafi-Rokni & Ataee, 2014;Burhayani, 2013;Kusnierek, 2016;Madani & Mahmoodi Nasrabadi, 2017;Mudawi, 2015;Razak & Yunus, 2016;Shakerian et al, 2016;Salcedo, 2010). Abdolmanafi-Rokni and Ataee (2014) claimed that background music help learners pay attention more to instructions and develop vocabulary retention in those who were exposed to music.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This finding corresponds with previous studies in which English learners could remember greater words following musical mnemonics sessions than non-musical learners (Abdolmanafi-Rokni & Ataee, 2014;Burhayani, 2013;Kusnierek, 2016;Madani & Mahmoodi Nasrabadi, 2017;Mudawi, 2015;Razak & Yunus, 2016;Shakerian et al, 2016;Salcedo, 2010). Abdolmanafi-Rokni and Ataee (2014) claimed that background music help learners pay attention more to instructions and develop vocabulary retention in those who were exposed to music.…”
Section: Discussionsupporting
confidence: 89%
“…According to Kusnierek (2016), using songs for teaching vocabularies is helpful in a way that it sticks the words into long-term memory and improve retention of words. Madani and Mahmoodi Nasrabadi (2017) showed that songs assist learners to remember new vocabularies easier and improve their vocabulary learning. Mudawi (2015) believed that songs and nursery rhymes are useful tools to help children absorb information like core words in learning language.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations